Analysis of Voice over IP Networks Service Quality Parameters Information - Jankūnienė, R.; Slanys, R.; Budnikas, A.; Gudonavičius, l. (Elektronika ir Elektrotechnika, 2005)
Actual questions for reducing amount of management information, transmitted over communications lines, are analyzed, i.e. an applying of factor analysis in examination of informative quality parameters for voice data transferring over IP. It was proposed to use main factors method, because it is unlimited in the input parameters quantity. It was defined from the using of empirical VoIP service data, that the most impact to the quality for functioning of all system has the parameters of packet delay and channel load. The possibility of VoIP service quality mistaken assessment for the service quality states determination can be minimized, having applied this method. Ill. 2, bibl. 13 (in English; summaries in Lithuanian, English and Russian).